2013
DOI: 10.1038/ng.2763
|View full text |Cite
|
Sign up to set email alerts
|

Dampening of expression oscillations by synchronous regulation of a microRNA and its target

Abstract: The complexity of metazoan organisms requires precise spatiotemporal regulation of gene expression during development. We find that in the nematode Caenorhabditis elegans approximately 2,000 transcripts undergo expression oscillations synchronized with larval transitions while thousands of genes are expressed in temporal gradients, similar to known timing regulators. By counting transcripts in individual animals, we show that the pulsatile expression of the microRNA (miRNA) lin-4 maintains the temporal gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(176 citation statements)
references
References 46 publications
12
163
1
Order By: Relevance
“…Conversely, vitellogenins are expressed only in the adult hermaphrodite intestine and are a hallmark of C. elegans development that can serve to determine the developmental stage of the worms (Blumenthal et al, 1984). Furthermore, gene-expression analysis has been used to cluster groups of genes that follow certain time-dependent oscillating patterns in developing C. elegans (Kim et al, 2013); hence, the extent of synchronization of these clusters can serve as a means to assess the extent of developmental synchronization in our experiments. The label-free quantification intensities for vitellogenins and two oscillating gene clusters as described in Kim et al (2013) plotted versus time were used to see which strains were synchronized properly in each experiment ( Figure S2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, vitellogenins are expressed only in the adult hermaphrodite intestine and are a hallmark of C. elegans development that can serve to determine the developmental stage of the worms (Blumenthal et al, 1984). Furthermore, gene-expression analysis has been used to cluster groups of genes that follow certain time-dependent oscillating patterns in developing C. elegans (Kim et al, 2013); hence, the extent of synchronization of these clusters can serve as a means to assess the extent of developmental synchronization in our experiments. The label-free quantification intensities for vitellogenins and two oscillating gene clusters as described in Kim et al (2013) plotted versus time were used to see which strains were synchronized properly in each experiment ( Figure S2).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, gene-expression analysis has been used to cluster groups of genes that follow certain time-dependent oscillating patterns in developing C. elegans (Kim et al, 2013); hence, the extent of synchronization of these clusters can serve as a means to assess the extent of developmental synchronization in our experiments. The label-free quantification intensities for vitellogenins and two oscillating gene clusters as described in Kim et al (2013) plotted versus time were used to see which strains were synchronized properly in each experiment ( Figure S2). From this assessment, we concluded that we had experiments in which strains were well synchronized to compare developing N2, daf-16(mu86) (CF1038), daf-2(e1370) (CB1370), and daf-2(e1370);daf-16(mu86) (DR1209) to one another and the strains expressing YFP (OW450) to those expressing a-synuclein-YFP (OW40).…”
Section: Resultsmentioning
confidence: 99%
“…This type of motif is particularly useful because it can counteract the effects of fluctuations in upstream components of the network. In C. elegans , for example, an IFFL involving both lin-4 and its target lin-14 ensures that variation in lin-14 mRNA levels are stabilized by synchronous oscillations in lin-4 [101]. The presence of miRNAs in IFFLs has also been associated with canalization mechanisms in vertebrates.…”
Section: Mechanisms Of Canalization By Mirnasmentioning
confidence: 99%
“…Although this kind of representation is informative, cellular resolution would provide more precise information. Recent examples of where this would be of value include sonic hedgehog signaling dynamics in the developing neural tube (Peterson et al, 2012) and the relationship between the expression level of a micro RNA and its target (Kim et al, 2013). In summary, our method facilitates the automated detection and quantification of transcripts and their assignment to cells and subcellular structures.…”
Section: Quantification Of Subcellular Transcript Distributionmentioning
confidence: 99%